Analysis and Performance Evaluation of Requirement Elicitation Techniques - Tiruneh, Theodros; Kumar Mishra, Manish (International Journal of Computer Sciences and Engineering, 2025)
The importance of requirements elicitation has been well recognized by the software development community. Clear and correct user requirement is critical to the success of software systems. There are numbers of requirements elicitation techniques available, which are used to understand and gather user requirements. In this paper, we have tried to analyze and evaluate the performance of different requirement elicitation techniques, which are under the categories of conversational, observational, analytic and synthetic methods of requirements elicitation. This study was performed in Ethiopia on analyst and requirement engineers working in various software development companies, staffs and senior students from University of Gondar who are involved in software development activities and bank employees who are involved in similar activities in their respective banks. In our study, we found that the requirement engineers prefer to use combination of different requirement elicitation methods. Interviews technique is the most preferred requirements elicitation technique in software development community followed by observation method.